(untitled) (Environment & Health, 2016)
Pollen of herbaceous anemophilous flora is an important factor of the seasonal allergy worldwide. If the main seasons of herbaceous plants’ pollen distribution, causing the symptoms of allergy, have been already determined and described for some regions of Ukraine, a long-term circadian distribution of such pollen concentrations has not been described in our country at all. Objective. We studied the changes in the concentrations of the herbaceous plants’ pollen grains during a day in the ambient air of the Central region of Ukraine by way of example of Vinnitsa city. Materials and Methods. Aerobiological study was performed with the application of the standard volumetric method during the seasons of 2012-2014. Results. We determined that different taxonomic groups of the herbaceous plants emitted intensively pollen in the ambient air from the beginning of May to the end of September. The largest pollen load was observed at 01.00 p.m. when the peak concentrations or concentrations similar to them of the pollen grains of the plants of Cannabaceae, Amaranthaceae, Polygonaceae families, ambrosia, Artemisia, plantain, nettle were registered in the air. There is a risk of pollinosis to the pollen grains of Artemisia, plantain, nettle, plants of Koeleria gracilis Pers, Astereaegenus and Polygonaceae families, including sorrel, in the period from 15.00 to 19.00. The residents of Vinnitsa can be affected the pollen grains of Artemisia, plantain, plants of Astereaegenus, Cannabaceae, Polygonaceae families in the interval from 07 to 11 a.m. Conclusions. We established that herbal plants’ pollen in the ambient air of Vinnitsa had mainly a local origin or migrated to the city from the adjoining territories and an increase of the concentrations of pollen grains in the air of a daytime indicated of it. Increases of the pollen concentrations were noted at night. It can be initiated by a transfer of the pollen grains of ambrosia, plantain, plants of Cannabaceae, Astereaegenus families at a long distance. Established circadian fluctuations of the allergenic pollen concentrations are an important contribution to the system of the prophylaxis of the symptoms of seasonal allergy developed in Vinnitsa.